Development of XY Micro-Position Stage Based on a Shape Memory Alloy (ELEKTRIKA- Journal of Electrical Engineering, 2021)
This paper reports a novel monolithic two DoF micro-positioning stage using shape-memory-alloy (SMA) actuator. The design was fabricated in a one fabrication step and it comprises all actuation functions in a single piece of SMA. The square shaped actuator has dimensions of 10 mm × 10 mm × 0.25 mm. The device includes a moving stage in the center which is connected to four SMA springs to generate large displacement in two directions, x- and y- axes. The four SMA actuators underwent annealing process using internal joule heating by flowing electrical current through the springs. Each of SMA springs has been actuated individually by internal joule heating generated using an electrical current. The developed design has been simulated to verify thermal response and heat distribution. In addition, the micro-positioning stage was experimentally tested. The maximum displacement results of the stage are 1.1 mm and 1.1 mm along the directions of x- and y- axes, respectively. The developed micro-positioning stage has been successfully demonstrated to control the position of a small object for microscopic imaging applications.